Optimalisasi Produksi Ayam Pejantan melalui Perbaikan Manajemen Pemeliharaan untuk Mendukung Ketahanan Pangan di Kelurahan Lempake, Samarinda - Akhmat Rizkuna; Roosena Yusuf; Amani Aldiyanti; Anhar Faisal Fanani; Nurul Fajrih; I Putu Gede Didik Widiarta; Dinar Anindyasari (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to enhance the productivity and welfare of local farmers through the optimization of male layer chicken production. Male chickens, often considered by-products of the laying hen industry, are generally overlooked and regarded as less economically viable. However, with the application of appropriate farming strategies, male chickens can become an important alternative source of protein to support food security. The methods implemented in this program include training on poultry management, the use of efficient locally-based feed, and the development of marketing strategies for the production output. The results of the program show a significant improvement in both productivity and the efficiency of male layer chicken farming among local farmers. With ongoing support, this program is expected to become a sustainable empowerment model in the small-scale livestock farming sector.